Evaluasi Sistem Informasi Manajemen Pelayanan Kepegawaian Elektronik (SIMPEL) di BKPSDM Kabupaten Serang - Mulyani, Ade; Budiati, Ayuning; Maulana, Delly (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
E-government has become a necessity for every agency to speed up access and services. The SIMPEL application at BKPSDM Serang Regency aims to create an effective and efficient paperless personnel service system. This research was to evaluate the SIMPEL application. This research implements the information systems model developed by Yusof,et al. This research was used to test whether the system quality, information quality, and quality service influence system use and user satisfaction, and test whether system use, user satisfaction and organizational structure have an effect on net benefit. This research used quantitative methodology with a sample of 58 respondents from SIMPEL users. Data was taken by respondents who filled out questionnaires and measured with a Likert scale. The data analysis method used is the Multiple Linear Regression Test using SPSS Version 26 software. Test indicates that system quality, information quality and service quality has influence on system usage and user satisfaction, while user satisfaction, system use and organizational structure has influence on the net benefit (level of significant α = 0.05).